Impacts of Water Bodies on Microclimates and Outdoor Thermal Comfort: Implications for Sustainable Rural Revitalization - Cheng, Yanyan; Liu, Xiao; Zeng, Zhi; Liu, Shengshuai; Wang, Zhaoyu; Tang, Xu; He, Bao-Jie (Frontiers in Environmental Science, 2022)
Water is the source of life and the fundamental element of ecology, while climate is inseparable from water. In order to evaluate the influence of water-adaptive space in a traditional Weizi (polder village) settlement on its microclimate, the authors analyzed the morphological characteristics of such polder village, and applied Envi-met in modelling to simulate the impact of water bodies and village morphological elements on human thermal comfort. This paper demonstrates the positive impact of water bodies on improving the thermal environment of a village and regulating its microclimate by quantifying the impact of morphological elements of the settlement on microclimate. The results of assessment indicate that: (1) The simulation model fits the actual measurements well with only small errors and it accurately reflects the experimental results; (2) In summer, the cooling effect of water bodies is better in the afternoon than in the morning, especially during 12:00 to 15:00. The cooling effect is significantly correlated with the distance to water bodies, i.e., the closer, the better; (3) Building density and man-made underlying surface are negatively correlated with temperature, humidity and PET value, while greening rate and water body rate are positively correlated with microclimate. Conclusion: Water bodies can improve outdoor comfort in summer and thus should be protected and developed in a rational and scientific manner. Villages can be built around water bodies for maximized cooling effect, and microclimate comfort can be effectively improved by increasing green plants near village center, and reducing man-made underlying surface and building density. The results of this study will provide guidance to the improvement of habitat environment in the process of rural revitalization, as well as the protection and re-development of traditional villages.